Characterization of CDOM in saline and freshwater lakes across China using spectroscopic analysis. (1st March 2019) - Song, Kaishan; Shang, Yingxin; Wen, Zhidan; Jacinthe, Pierre-Andre; Liu, Ge; Lyu, Lili; Fang, Chong
Abstract: Colored dissolved organic matter (CDOM) is a major component of DOM in waters, and plays a vital role in carbon cycling in inland waters. In this study, the light absorption and three-dimensional excitation-emission matrix spectra (EEMs) of CDOM of 936 water samples collected in 2014–2017 from 234 lakes in five regions across China were examined to determine relationships between lake water sources (fresh versus saline) and their fluorescence/absorption characteristics. Results indicated significant differences regarding DOC concentration and a CDOM (254) between freshwater (6.68 mg C L −1, 19.55 m -1 ) and saline lakes (27.4 mg C L −1, 41.17 m -1 ). While humic-like (F5 ) and fulvic-like (F3 ) compounds contributed to CDOM fluorescence in all lake waters significantly, their contribution to total fluorescence intensity (FT ) differed between saline and freshwater lakes. Significant negative relationships were also observed between lake altitude with either F5 (R 2 = 0.63, N = 306) or FT (R 2 = 0.64, N = 306), suggesting that the abundance of humic-like materials in CDOM tends to decrease with increased in lakes altitude. In high-altitude lakes, strong solar irradiance and UV exposure may have induced photo-oxidation reactions resulting in decreased abundance of humic-like substances and the formation of low molecular weight compounds. These findings have important implications regarding our understanding of C dynamics in lacustrine systems and the contribution of these ecosystems to the global C cycle. Graphical abstract: Highlights: The 936 lake samples in China were examined to explore CDOM optical properties. FRI was used to characterize CDOM sources of saline waters and fresh waters. The relationships between CDOM absorption and FDOM components were analyzed. Close relations of elevation and saline waters FDOM components were identified.